The level of physical activity of undergraduate students at three faculties over a seven-day period - Fučkar Reichel, Ksenija (Array, 2014)
Regular physical activity stimulates at the level of the whole body a series of positive adaptive transformations that contribute to the enhancement of functional capabilities, and advance health and quality of life. Our study includes 2000 undergraduate students (M=47.98% ; F=48.98%, and the rest of forms were not usable) of the first year at the three institutions of higher education in Zagreb. The goal of our study was to determine the level of physical activity over the last seven days with the criterion of minimum of 30 minutes of physical activity per day, and if there is difference between genders of students from different faculties. The results show that the level of physical activity over the last seven days in male students is higher than in the female students, particularly evident in the level of physical activity in 3 days and more. The most active students are of the Technical Polytechnic of Zagreb, and they are the most statistically distinguished group in out study.